A Serrin-type problem with partial knowledge of the domain. (July 2021) - Dipierro, Serena; Poggesi, Giorgio; Valdinoci, Enrico
Abstract: We present a quantitative estimate for the radially symmetric configuration concerning a Serrin-type overdetermined problem for the torsional rigidity in a bounded domain Ω ⊂ R N, when the equation is known on Ω ∖ ω ¯ only, for some open subset ω ⋐ Ω . The problem has concrete motivations in optimal heating with malfunctioning, laminar flows and beams with small inhomogeneities.